PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KAYONG UTARA - B11107083, JIMMY JUWARDI (Jurnal Manajemen Update, 2013)
The title of this research is The Influence of OrganizationalCultureOnEmployee PerformanceDepartment of Revenue, Finance and Asset ManagementDistrictNorthKayong. The problem of this research is how big influence oforganizational cultureonemployeeperformanceonthe Department of Revenue, Finance and Asset ManagementDistrictNorthKayong. This research has purpose to know how Influence of OrganizationalCultureOnEmployee PerformanceDepartment of Revenue, Finance and Asset ManagementDistrictNorthKayong. The method of this research is descriptive. The Populations have 40 people and so the sample. This research uses analysis quantitative with the tool of analysis is multiple linear regression with F test and t Test to test independent variable to dependent variable. The significant value which use in this research is 0.05. The result of the adjusted R square are 0,093 it means the influence of innovation and take a risk (X1), attention to something details (X2), orientation to result (X3), orientation to people (X4), orientation to team (X5), agressitivity (X6), and stability (X7) only contributesto employee performanceby9.3%, while 90.7% is influencedby other factors outsidethe study. The result of this research show simultantly variable organization culture has not significant influence to employees performance (Sig F = 0,179 < 0,05) and partial variable has significant influence to performance (Y) are variable orientation to team (X5) with the value of t is 2,301 or significant value is 0,028 < 0,05. And the others variables are like innovation and take a risk (X1),attention todetail(X2), orientation to result (X3), orientation to people (X4), agressitivity (X6), and stability (X7), have significant value > 0,05 so it doesnt give influence in parsial to employees performance (Y) Keywords :organizational culture, employees working performance, department of revenue, finance,asset management